Nanocarriers of Fe3O4 as a Novel Method for Delivery of the Antineoplastic Agent Doxorubicin Into HeLa Cells in vitro - Xia, Kun-kun; Lyu, Yong; Yuan, Wei-tang; Wang, Gui-xian; Stratton, Harrison; Zhang, Shui-jun; Wu, Jie (Frontiers in Oncology, 2019)
Here we report the synthesis and in vitro characterization of a redox-sensitive, magnetically inducible nanoparticle carrier system based on doxorubicin (DOX) drug delivery model. The quantal nanocarrier unit consists of a magnetite Fe3O4 nanoparticle core that is further encapsulated in self-assembled micelles of the redox-responsive polyethylene glycol derivative, DSPE-SS-mPEG. The nanocarrier system was prepared using a combination of ultrasonication and dialysis to produce the microenvironment sensitive delivery system. The final synthesized and DOX-loaded magnetic nanocarriers had an average size of ~150 nm when assembled with a 6.9% DOX payload. The release rate of DOX from these redox-responsive magnetic nanocarriers was shown to be accelerated in vitro when in the presence of glutathione (GSH). Furthermore, we demonstrated that more redox-responsive magnetic nanocarriers could be taken up by HeLa cells when a local magnetic field was applied. Once internalized within a cell, the micelles of the outer nanocarrier complex were broken down in the presence of higher concentrations of GSH, which accelerated the release of DOX. This produces a particle with dual operating characteristics that can be controlled via a specific cellular environment coupled with an exogenously applied signal in the form of a magnetic field triggering release.